“Estudio del estilo periodístico utilizado en la sección deportiva del diario regional los Andes, periodo enero – julio de 2018.” - Jimmy Javier, Tuquerres Gualavisi (2020)
This research work is focused on identifying the journalistic style used by the sports section of Regional Newspaper “Los Andes”, in the period January-July 2018, the media can reach various communities and their mission is to inform, that is why the printed media uses journalistic styles and genres, expression features that are characteristic of the genres, with their structure and elaboration methods. The investigation of the inductive-deductive method: which allowed to analyze the news from the sports section of DRILA with a matrix with theoretical bases, and determine the journalistic style that it uses, the totality of analyzed notes 1662 and 2 interviews, who for their experiences as publishers in the printed media that provided arguments to understand information management. The result, the style that DRILA uses in the sport section is: informative with 58%, interpretive with 40%, editorial 2% pleasant literary 0%. The genres in which the information are presented: the news 57%, chronic 40%, short, critical column, article with 1%, the other genres and that are involved in the opinion of the medium found 0%. With 90%, it was found that DRILA uses a clear language in the sport section, the use of concise language with 9% and natural language with 1%. It is decided to establish one of the strategies that the newspaper use today, which is the implementation of a manuals for Journalistic Style, in order to have a guide to follow in the treatment of information, using the Manual you can generate elaborate news, investigation, which provide an added value of space, time and criteria.